Assessment of the competition level in the sector of bicycle manufacturers in the Slovak Republic - Hojdik Vladimír; Raková Monika (SHS Web of Conferences, 2021)
Bicycle industry has recorded significant boom recently, mainly as a consequence of global pandemic situation, but also as a result of green policies of countries. The popularity of cycling is on its all-time high, which also transferred to rising sales of bicycles worldwide. This paper evaluates current situation of bicycle industry in Slovak republic, mainly with the objection on performance of Slovak bicycle producers. With use of appropriate indicators, the paper aims to assess the rate of competitiveness among Slovak bicycle producers. For this purpose, relevant indicators as market share, concentration ratio CR3, CR5, and Herfindahl index are calculated and evaluated. The aim of this paper is to analyze financial results of Slovak bicycle industry producers, then measure the degree of concentration of whole industry in order to explain industry competitiveness in context of Slovak economy.